2017
DOI: 10.1371/journal.ppat.1006545
|View full text |Cite
|
Sign up to set email alerts
|

The AraC Negative Regulator family modulates the activity of histone-like proteins in pathogenic bacteria

Abstract: The AraC Negative Regulators (ANR) comprise a large family of virulence regulators distributed among diverse clinically important Gram-negative pathogens, including Vibrio spp., Salmonella spp., Shigella spp., Yersinia spp., Citrobacter spp., and pathogenic E. coli strains. We have previously reported broad effects of the ANR members on regulators of the AraC/XylS family. Here, we interrogate possible broader effects of the ANR members on the bacterial transcriptome. Our studies focused on Aar (AggR-activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 54 publications
3
28
0
Order By: Relevance
“…In addition to the already reported Aar-dependent modulation of H-NS2 ( 31 ), we show here that, unlike H-NS, H-NS2 shows temperature- and nutrient-dependent regulation. With respect to temperature, H-NS2 expression is higher at 37°C than at 25°C.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In addition to the already reported Aar-dependent modulation of H-NS2 ( 31 ), we show here that, unlike H-NS, H-NS2 shows temperature- and nutrient-dependent regulation. With respect to temperature, H-NS2 expression is higher at 37°C than at 25°C.…”
Section: Discussionsupporting
confidence: 83%
“…It has been recently shown that the plasmid-encoded AraC negative regulator Aar modulates expression of both H-NS and H-NS2 in E. coli strain 042 ( 31 ). We decided to investigate whether, in addition to Aar, environmental or physiological factors influence H-NS2 expression.…”
Section: Resultsmentioning
confidence: 99%
“…In EAEC, regulation of virulence is mediated by AggR and its negative regulator Aar. Aar controls the expression of at least 210 genes; one-third of these genes are related to metabolism and transport [ 24 ]. We sought to determine the relevance of AggR/Aar-mediated regulation of metabolic pathways in EAEC by performing untargeted metabolomic analysis of EAEC042 and EAEC042 aar .…”
Section: Resultsmentioning
confidence: 99%
“…Since PE and LysoPE species serve as the donor of fatty acids in the N-acylation of apolipoproteins generating lysophospholipids as products of degradation by action of N-acyltransferases, we sought to identify AggR/Aar-regulated proteins with N-acyltransferase activity. With this purpose, we took advantage of previously reported microarray and RNAseq data from EAEC 042 aggR and EAEC 042 aar strains [ 8 , 24 ], which identified one potential hypothetical N-acyltransferase; AatD (CBG27765.1, EC042_pAA011) [ 8 , 25 ]. AatD is encoded in the aat operon and its function remains obscure [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Illnesses caused by the foodborne enteropathogen and Shiga toxin-producing Escherichia coli O157 (STEC) can be lifethreatening (Nataro and Kaper, 1998;Law, 2001;Santiago et al, 2017). Most of the STEC strains identified by USDA carry toxin genes stx1a and stx2a (González-Escalona and Kase, 2019).…”
Section: Introductionmentioning
confidence: 99%